First person - Alec Nickolls (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Alec Nickolls is first author on 'Human embryoid bodies as a 3D tissue model of the extracellular matrix and α-dystroglycanopathies', published in DMM. Alec conducted the research described in this article while a PhD student in Carsten Bönnemann's lab at National Institute of Neurological Disorders and Stroke, National Institutes of Health, Bethesda, MD, USA. He is now a postdoctoral fellow in the lab of Alexander Chesler at National Center for Complementary and Integrative Health, National Institutes of Health, Bethesda, MD, USA, investigating engineered cellular systems for disease modeling and drug discovery.